Minat Belajar Siswa Terhadap Mata Pelajaran Pendidikan Agama Kristen (Studi Kasus di SMA Negeri 14 Ambon) - Hendra Helwaun (Journal on Education, 2024)
The research carried out aims to determine the learning interest of class XI IPS students at SMA Negeri 14 Ambon, as well as various factors that influence students' learning interest. Data collection was carried out using observation, questionnaire and interview techniques. The data analysis technique was carried out using two research methods, namely the qualitative data analysis method which used data reduction, data presentation and conclusions, while the quantitative data analysis method used the questionnaire distribution technique. The level of student interest in learning PAK can be seen in four learning indicators, namely feelings of enjoyment towards PAK subjects, interest in PAK subjects, students' enthusiasm for participating in PAK learning, and students' attention to the teacher. Meanwhile, the factors that cause students' interest in learning to be low can be seen in the interview results which are divided into two, namely internal factors (within the student) and external factors (from outside the student). Based on this research, the author concludes that students' interest in learning in class XI IPS still needs to be improved. Factors that hinder learning need to be considered, not only an educator who plays a role in increasing students' interest in learning but also assisted by parents and the environment where children learn so that children are motivated to increase their interest in learning.